Diabetes mellitus and the healing of periapical lesions in root filled teeth: a systematic review and meta‐analysis. (15th August 2020) - Gupta, A.; Aggarwal, V.; Mehta, N.; Abraham, D.; Singh, A.
Abstract: Background: Diabetes mellitus (DM) may affect the healing and survival of root filled teeth with periapical lesions. Aim: To systematically analyse the available clinical literature to evaluate the association between DM and the prevalence of radiolucent periapical lesions in root filled teeth. The review question was 'Is there a difference between the root canal treatment healing outcome (in terms of presence or absence of radiolucent periapical lesions) in diabetic and non‐diabetic patients?'. Data sources: A systematic review of cross‐sectional studies and prospective clinical trials was conducted according to the PRISMA checklist. The review involved a search of the electronic databases of PubMed, Scopus and EBSCO host. Study eligibility criteria, participants and interventions: The research protocol was previously registered in the International Prospective Register of Ongoing Systematic Reviews (CRD42019130954) and included defined inclusion/exclusion criteria. The included studies were related to the root canal treatment outcome in diabetic patients in terms of periapical radiolucent lesions associated with root filled teeth. Study appraisal and synthesis: The selected studies were critically analysed by two evaluators using the Joanna Briggs Institute Critical Appraisal tool. The pooled odds ratio (OR) was recognized as the primary outcome variable and measure of the effect for the occurrence of periapical lesions associated with root filled teeth of control and diabetic patients. The random‐effects Mantel–Haenszel method was used, at a 95% confidence interval, to calculate the pooled OR. A funnel plot was created to evaluate possible sources of heterogeneity. Results: Ten studies published between 1989 and March 2019 were selected after thorough analysis and exclusion according to the strict criteria. Seven cross‐sectional studies, 1 longitudinal and 2 prospective clinical studies were included. The pooled OR was calculated by comparing 773 diabetic subjects and 1133 control subjects. The pooled OR for the observational studies and clinical studies were 1.42 and 6.36, respectively. This value signified a high prevalence of periapical lesions in root filled teeth in diabetic subjects. Limitations: There are limited prospective clinical trials on this topic. The majority of the included studies are observational. Conclusions and implications of key findings: The data suggest a strong connection between the presence of periapical radiolucency on root filled teeth amongst diabetics as determined by the pooled OR.